Uruguay : Technical Assistance Report-Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report, 2021)
At the request of the Central Bank of Uruguay (BCU), and with the support of the International Monetary Fund's (IMF's) Western Hemisphere Department (WHD), a monetary and financial statistics (MFS) technical assistance (TA) mission from the IMF's Statistics Department (STA) visited Montevideo during February 3-14, 2020. The main objectives of the mission were to: (i) review available source data for other financial corporations (OFC); in particular, insurance corporations (IC), pension funds (PF), and credit administration companies (CAC); and (ii) compile standardized monetary statistics for OFC (report form SRF 4SR) in line with the 2016 Monetary and Financial Statistics Manual and Compilation Guide (MFSMCG). The officials met during the mission are listed in Appendix I.